DIVORCE IN THE DIGITAL AGE: THE IMPACT OF SOCIAL MEDIA ON HOUSEHOLD UNITY FROM A SHARIA LAW PERSPECTIVE - Muhammad Afdhal Zikri; Jumni Nelli; Kasmidin (SOSIOEDUKASI, 2026)
The development of social media in the digital era has brought significant changes to the dynamics of household life, particularly in marital relations. Social media not only functions as a means of communication but also has the potential to trigger conflict that can lead to divorce if not used wisely. This study aims to analyze the impact of social media on household integrity and divorce from the perspective of Sharia law in Indonesia. The study used a qualitative approach with normative legal methods, enriched with empirical analysis through literature reviews and Religious Court decisions. The results show that social media acts as an accelerator of household conflict through digital jealousy, emotional infidelity, and unhealthy communication. From a Sharia legal perspective, these phenomena contradict the principles of mu'āsyarah bil ma'ruf, hifz al-'irdh, and the purpose of marriage to create a sakinah, mawaddah, and rahmah family. This study emphasizes the importance of strengthening digital literacy based on Islamic values and an adaptive and contextual approach to Islamic family law in responding to the challenges of divorce in the digital era.